The Influence of Managerial Ability on Investor Reactions: A Study on Manufacturing Companies Listed on the Indonesia Stock Exchange from 2000 to 2022 - Widjoyo, Stephen Suryo; Hendrawaty, Ernie (LPPPIPublishing, 2025)
This study examines the influence of managerial capabilities on investor reactions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2000 to 2022. Using panel data from 80 companies and employing regression analysis, the study explores how managerial ability impacts abnormal returns (AR) and trading volume activity (TVA). The results reveal that managerial capabilities significantly and negatively affect AR, suggesting that competent management enhances investor confidence and corporate performance, leading to increased returns. However, managerial ability does not have a significant impact on TVA, indicating that investor reactions in terms of trading activity may be influenced by other factors, such as macroeconomic conditions or short-term financial performance. The findings support previous research on the importance of management quality in shaping investor behavior but highlight the different ways managerial skills influence market outcomes. The study contributes to understanding how managerial decisions affect stock market performance and provides implications for both investors and corporate managers in fostering investor trust and sustainable business growth.